2013
DOI: 10.1002/er.3126
|View full text |Cite
|
Sign up to set email alerts
|

Conducting carbon/polymer composites as a catalyst support for proton exchange membrane fuel cells

Abstract: SUMMARY Carbon/poly(3,4‐ethylene dioxythiophene) (C/PEDOT) composites are synthesized by in situ chemical oxidative polymerization of EDOT monomer on carbon black in order to decrease carbon corrosion that occurred in carbon‐supported catalysts used in proton exchange membrane fuel cell. The effects of different dopants including polystyrene sulfonic acid, p‐toluenesulfonic acid and camphorsulfonic acid with the addition of ethylene glycol or dimethyl sulfoxide on the properties of the composites are investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
1
15
2
Order By: Relevance
“…The PEM fuel cell polarization curves and the corresponding power density curves of all catalysts are shown in Figure ; to provide a balance between cell efficiency and power output, the performances of the catalysts were mostly evaluated at a cell voltage of 0.6 V at which the measured current and power densities are affected by the ORR activity of the metal catalyst. PEM fuel‐cell performance for PEDOT/C supported catalyst in our previous study was worse than that reported in this study. The reason for this may be explained by the modification of the humidifier of the system used in our fuel‐cell test station, which was modified by taking the filling material out of the humidifier.…”
Section: Resultscontrasting
confidence: 94%
See 2 more Smart Citations
“…The PEM fuel cell polarization curves and the corresponding power density curves of all catalysts are shown in Figure ; to provide a balance between cell efficiency and power output, the performances of the catalysts were mostly evaluated at a cell voltage of 0.6 V at which the measured current and power densities are affected by the ORR activity of the metal catalyst. PEM fuel‐cell performance for PEDOT/C supported catalyst in our previous study was worse than that reported in this study. The reason for this may be explained by the modification of the humidifier of the system used in our fuel‐cell test station, which was modified by taking the filling material out of the humidifier.…”
Section: Resultscontrasting
confidence: 94%
“…The XRD pattern of Pt:PEDOT/C catalysts shows characteristic sharp peaks at 2 θ ≈39.8, 46.6, 67.5, and 81.5°corresponding to the (1 1 1), (2 0 0), (2 2 0), and (3 1 1) lattice planes of Pt, respectively, confirming the presence of Pt in the face‐centered cubic (FCC) structure. The peak at 2 θ ≈26° corresponds to PEDOT and C, which is overlapped . The average sizes of the Pt particles were determined by using the Scherrer equation after curve fitting and background subractions and by using peak broadening of Pt (2 2 0), which is not affected by carbon overlapping, and are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows the X‐ray diffravtion (XRD) patterns of the as‐prepared Fe x NC‐T‐2 samples with different pyrolysis temperature and different Fe content. For the samples obtained at relatively lower temperatures such as 600°C and 700°C, only one broad diffraction peak corresponding to the (002) crystal plane of graphite carbon was detected . This peak shifted from 28.0° to 26.4° when the pyrolysis temperature increased from 600°C to 700°C, suggesting that the layer spacing of carbon is increased after N doping under relatively high temperature.…”
Section: Resultsmentioning
confidence: 95%
“…The carbon structure has a strong influence on the anchoring effect of metal and auxiliary atoms on its surface, which is crucial in providing fixed reaction sites for the reactants . Various types of carbons, such as carbon black, multiwall carbon nanotubes (MWCNTs), activated carbon, C/polymer composite, and graphene, have been identified as key potential catalyst support materials in fuel cells. The use of carbon nanostructures was shown to significantly increase the current density, durability, and stability of the electrode due to the increase in the specific surface area and a strong anchoring effect.…”
Section: Introductionmentioning
confidence: 99%